An Overview of the Indonesian Security Outlook - Permatasari, Diah Ayu (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2015)
Security issue has always become a major problem for every sovereign state. Tremendous changes to the world society these days for example through advance technologies, extreme perception of the religious beliefs, people movement across the globe, and economic disparity, had oblige sovereign states to adjust significantly towards its security policy. Indonesia, an archipelagic, with its strategic location and diverse community has always at the crossroad to overcome the security challenges that occurs since Independence Day in 1945 until recent days. This article will briefly define Indonesia’s security policy, and discussing possible ways to deterrence conflicts through strengthening the main tools of internal defenses and beneficial international cooperation in security. Contemporary Second track Indonesia foreign policy stands on the basic of the international cooperations on security to protect the people and interests.